Analysis of the relationship between hamstring flexibility with muscular strength and its response to myofascial release - Spinoso, Deborah Hebling; Goulart, Murilo; Ferreira, Antonio; Navega, Marcelo (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Decreased flexibility can contribute to postural changes, the deficit in the ability to produce strength, and predispose to injuries. Currently, several myofascial release techniques work to improve muscle flexibility. Objective: To analyze the relationship between flexibility and muscle strength of the knee flexors and to verify the acute effect of two modalities of myofascial release on the flexibility of the hamstrings. Methods: 45 women participated in this study, divided into Manual Release Group, Instrumental Release Group, and Control Group. A sit and reach test, a third finger floor test, an assessment of the popliteal angle, and an assessment of knee flexion muscle strength were performed. Subsequently, the volunteers received a myofascial release session in the hamstring muscle group. After treatment, the volunteers were reassessed. Results: Both groups that received myofascial release performed better in flexibility tests. There was no correlation between hamstring flexibility and the ability to produce joint torque from knee flexion. Conclusion: The flexibility of the hamstring muscles did not influence the ability to produce knee flexion torque and both myofascial release techniques were effective in improving the flexibility of this musculature.